Cost Efficiency and Loan Loss Provision Analysis in Vietnamese banks - Nguyen, Linh Chi (2019)
This study analyses cost efficiency and loan loss provisioning behaviour of 33 Vietnamese commercial banks over the period of 2011 to 2018. Along with testing three hypotheses of loan loss provision, including income smoothing, capital management and business cycle, the results of cost efficiency score are included in the model to examine their relationship proposed by Berger and DeYoung (1997). This study first estimates banks’ efficiency levels from a translog cost function. Then, we incorporate the estimated efficiency results into the regression of loan loss provisions using Generalized Method of Moments (GMM) estimators. The empirical results show that the average of Vietnamese banks efficiency score is above 92% and support for the existence of the income smoothing and capital management hypotheses, whereas no evidence is found for business cycle. Furthermore, a significant negative relationship between loan loss provisions and the banks efficiency is indicated.